Interleukin-13 receptor alpha 2 cooperates with EGFRvIII signaling to promote glioblastoma multiforme. Issue 1 (December 2017) - Newman, Jennifer; Wang, Grace; Arima, Kazuhiko; Guan, Shou; Waters, Michael; Cavenee, Webster; Pan, Edward; Aliwarga, Edita; Chong, Siao; Kok, Catherine; Endaya, Berwini; Habib, Amyn; et al.
Abstract The interleukin-13 receptor alpha2 (IL-13Rα2) is a cancer-associated receptor overexpressed in human glioblastoma multiforme (GBM). This receptor is undetectable in normal brain which makes it a highly suitable target for diagnostic and therapeutic purposes. However, the pathological role of this receptor in GBM remains to be established. Here we report that IL-13Rα2 alone induces invasiveness of human GBM cells without affecting their proliferation. In contrast, in the presence of the mutant EGFR (EGFRvIII), IL-13Rα2 promotes GBM cell proliferation in vitro and in vivo. Mechanistically, the cytoplasmic domain of IL-13Rα2 specifically binds to EGFRvIII, and this binding upregulates the tyrosine kinase activity of EGFRvIII and activates the RAS/RAF/MEK/ERK and STAT3 pathways. Our findings support the "To Go or To Grow" hypothesis whereby IL-13Rα2 serves as a molecular switch from invasion to proliferation, and suggest that targeting both receptors with STAT3 signaling inhibitor might be a therapeutic approach for the treatment of GBM. Interleukin-13 receptor alpha 2 is highly expressed in glioblastoma multiforme but its role in this malignancy is unclear. Here the authors show that this receptor interacts with mutant EGFR, stimulating its kinase activity, thus inducing proliferation.